Scot Harvath : Code of Conduct - Book 14 - Thor, Brad (New York : Pocket Books, 2016)
"Hidden deep within one of the worlds most powerful organizations is a secret committee with a devastating agenda. Its members are afforded incredible protections-- considered elites, untouchables. But when four seconds of video is captured halfway around the world and anonymously transmitted to D.C., covert wheels are set in motion, and counterterrorism operative Scot Harvath is tapped to undertake the deadliest assignment of his career. What begins as a favor will evolve into a globe-spanning drama of highly personal stakes played out against a backdrop of stunning international intrigue, duplicitous political gamesmanship, and the darkest, most clandestine fears of the espionage world"--
Keywords: Harvath, Scot (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention; Fiction; Thrillers (Fiction)